Містерія й карнавал як метаформи постпостмодерністського британського роману - Дроздовський, Д. (Філологічний дискурс, 2019)
У статті йдеться про реалістичні тенденції, експліковані в сучасному британському романі. Розвинуто концепцію Б. Шалагінова про містерію й карнавал як два метажанри світової літератури. Доведено, що в англійському романі «Хмарний атлас» Д. Мітчелла репрезентовано карнавальні та містеріальні елементи, причому центральне місце посідає саме містерія, яка переживає занепад у літературах ХХ ст. З’ясовано, що в британській постпостмодерністській літературі відбувається співіснування двох зазначених метаформ. Окреслено світоглядну специфіку (пост)реалізму, експлікованого в сучасному романі Великої Британії. Наголошено на аспектах медикалізованого пізнання дійсності персонажами. Визначено, що оприявнені в романах конфлікти, соціальні непорозуміння, комунікативні девіації тощо зображені як приклади фізіологічних порушень персонажів («Дивний випадок із собакою вночі», «Угамуйте мене», «Субота»), а отже, сучасний британський роман акцентує на детермінації соціальних феноменів біологічними особливостями й фізіологічною специфікою літературних героїв. In the paper, the author deals with realistic tendencies explicated in contemporary British novel. B. Shalahinov’s theory of the mystery and carnival as two metaforms of world literature has been developed. It has been proved that in the contemporary English novel «Cloud Atlas» by D. Mitchell the carnival and mysterious elements are represented, and the mystery occupies a central place. It is found out that in British post-postmodernistic literature there is a coexistence of two mentioned metaforms. The aspects of medicalized knowledge of reality by the characters have been emphasized. It is determined that conflicts, social misunderstandings, communicative deviations, etc. presented in the novels are depicted as examples of physiological violations of characters («The Curious Incident of the Dog in the Night-Time», «Carry me down», «Saturday»), and therefore, contemporary British novel focuses on determination of social phenomena by biological peculiarities and physiological specificity of literary heroes. The specificity of the representation of reality in the contemporary British novel confirms D. Nalivayko’s ideas about realism as a world-view and stylistic tendency that manifests itself in different cultural epochs. The realistic mode of writing, in essence, becomes a factor that determines scientific («Saturday») or at least the rationalized («The Curious Incident of the Dog in the Night-Time», «Carry me down») vision of reality by characters who, by means of the critical pure mind (Christopher, John, Sonny~451) carry out audits of the surrounding reality revealing the forms of political and media manipulations, the hidden policy of colonialism, etc. In British post-postmodernistic novel, realistic strategies for the image of reality have a medicalized bias. In contemporary English novel of 2000-2010s, the category of lifeworld is presented as determined by genetic diseases and psychological deviations caused by the traumatized memory. In any case, the post-postmodernistic (post)realistic tendencies represent at biological and physiological feathers that give an opportunity to disclose the nature of social conflicts and even interethnic confrontations. At the same time, the realistic presentation of simultaneous carnival and mysterious elements in contemporary British novel, and the scientifically oriented mind of the characters who perceive the reality as a carnival (social dimension) and a mystery (metaphysical dimension) determine specific features of contemporary British literary process.